Brazilian Portuguese version of the Amsterdam infant stool scale: a valid and reliable scale for evaluation of stool from children up to 120 days old - de Deus Silva, Laura Cantisano [UNESP]; Bianchini, Priscila Monaro [UNESP]; Ortolan, Erika Veruska Paiva [UNESP]; Hamamoto, Juliana Fattori [UNESP]; Fermiano, Rosemary [UNESP]; Rego, Rebeca Mayara Padilha [UNESP]; Lyra, João César [UNESP]; Benninga, Marc Alexander; de Arruda Lourenção, Pedro Luiz Toledo [UNESP] (Springer Nature, 2021)
Background: For newborns and infants wearing diapers the difficulties in characterizing the appearance of the stool are significant, since the changes in consistency, quantity, and color of the stool are higher than in other age groups. The Amsterdam Infant Stool Scale (AISS) was created and validated in 2009, providing a specific tool for the evaluation of the stool of children up to 120 days old. However, to be used in clinical practice and scientific investigations in Brazil, it is mandatory to perform the translation and cross-cultural adaptation process for Brazilian Portuguese language. Thus, we aim to perform the translation and cross-cultural adaptation of AISS into Brazilian Portuguese and to evaluate the psychometric properties of the translated version. Methods: The process of translation and cross-cultural adaptation was performed according to the internationally accepted methodology, including: translation, summary of translations, backtranslation, preparation of the pre-final version, application of the pre-test and determination of the final version. The evaluation of the psychometric properties was performed through the application of Brazilian Portuguese AISS, by five examiners (including child health field specialists and a literate adult lay on the subject), analyzing 238 stool photographs of children under 120 days old. The intra and inter-examiner agreement values were determined using kappa statistic. The validity of the criterion was investigated through correlation analysis (Kendall’s coefficient) between the classifications determined by the non-specialist examiner and the expert examiners. Results: In all 30 tests performed between different examiners, there was an agreement considered as at least moderate (kappa values above 0.40). The intra-examiner reliability was considered as substantial (kappa> 0.6). There was a statistically significant correlation (p < 0.05) between the classifications determined by the examiners considered as specialists and the examiner considered as non-specialist. Conclusion: The Brazilian Portuguese AISS version proved to be valid and reliable to be used by healthcare professionals and the general public in the evaluation of stool from children up to 120 days old.
Keywords: Defecation; Infant; Newborn; Reproducibility of results; Translations